Philippine bureaucratic capacity for effective governance and development - Aguja, Hilton J. (Langkit : the Official journal of the College of Arts & Social Sciences Mindanao State University-Iligan Institute of Technology, 2006)
The economic success stories of the high performing Asian economies (HPAES) show that economic growth and development is anchored on the capacity of the State to steer the economy along politically-defined priorities. That growth requires a strong state with its concomitant bureaucratic capacity for planning and policy implementation is the lesson to be learned in these experiences.